Geração de dados GPS de pseudodistância para uma estação virtual: Métodos, implementação e análise dos resultados - Alves, Daniele Barroca Marra [UNESP]; Monico, João Francisco Galera [UNESP] (My University, 2010)
This paper aims to evaluate the quality of the pseudorange observables generated for a Virtual Reference Station (VRS). In order to generate the VRS data three different approaches were implemented and tested. In the first one, raw data from the reference station network were used while in the second it was based on double difference reference station corrections. Finally, in the third approach atmospheric models (ionosphere and troposphere) were used to create the VRS data. Sao Paulo State Network stations were used in all experiments. The VRS data were generated in a reference station position of known coordinates (real file). In order to validate the approaches, the VRS data were compared with the real data file. The results were quite similar, reaching the decimeter or centimeter level, depending on the approach applied.
Generating GPS pseudorange data for a virtual station: Methods, implementation, and analysis of results
Keywords: Network-based positioning; Pseudorange; Vrs